Low-Level Laser Therapy Effects on Rat Blood Hemostasis Via Significant Alteration in Fibrinogen and Plasminogen Expression Level: Low Level Laser Therapy Effects on Rat Blood Hemostasis - Arjmand, Babak; Khodadoost, Mahmood; Jahani Sherafat, Somayeh; Rezaei-Tavirani, Mostafa; Ahmadi, Nayebali; Okhovatian, Farshad; Rezaei Tavirani, Majid (Journal of Lasers in Medical Sciences, 2021)
Introduction: There are many documents about the significant role of low-level laser therapy (LLLT) in different processes such as regenerator medicine and bone formation. The aim of this study is to assess the role of LLLT in blood hemostasis in rats via bioinformatic investigation. Methods: The differentially expressed plasma proteins of treated rats via LLLT from the literature and the added 50 first neighbors were investigated via network analysis to find the critical dysregulated proteins and biological processes by using Cytoscape software, the STRING database, and ClueGO. Results: A scale-free network including 55 nodes was constructed from queried and added first neighbor proteins. Fibrinogen gamma, fibrinogen alpha, and plasminogen were highlighted as the central genes of the analyzed network. Fibrinolysis was determined as the main group of biological processes that were affected by LLLT. Conclusion: Findings indicate that LLLT affects blood hemostasis which is an important point in approving the therapeutic application of LLLT and also preventing its possible complication. DOI: 10.34172/jlms.2021.59